2019
DOI: 10.1111/adb.12719
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine'omics: Genome‐wide and transcriptome‐wide analyses provide biological insight into cocaine use and dependence

Abstract: We investigated the genetic and molecular architecture of cocaine dependence (CD) and cocaine use by integrating genome-/transcriptome-wide analyses. To prioritize candidates for follow-up investigation, we also sought to translate gene expression findings across species. Using data from the largest genome-wide association study (GWAS) of CD to date (n = 3176, 74% with CD), we assessed genomic heritability, gene-based associations, and tissue enrichment. We detected a significant singlenucleotide polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…Integrating genome‐wide genetic findings with tissue‐specific gene expression genetics could reveal additional biological mechanisms underlying substance dependence. Using this approach, Huggett and Stallings have identified a SNP associated with cocaine dependence and detected three genes (two loci) underlying this predisposition that displayed robust enrichment in numerous brain regions, including the hippocampus . Gene expression genetic analyses in the GTEx project show sex differences in genetic regulation of gene expression in both reproductive and nonreproductive tissues, providing an important means of evaluating the mechanisms through which sex‐specific genetic loci might act.…”
Section: Sex Differences In Human Genomic Studies Of Addictionmentioning
confidence: 99%
“…Integrating genome‐wide genetic findings with tissue‐specific gene expression genetics could reveal additional biological mechanisms underlying substance dependence. Using this approach, Huggett and Stallings have identified a SNP associated with cocaine dependence and detected three genes (two loci) underlying this predisposition that displayed robust enrichment in numerous brain regions, including the hippocampus . Gene expression genetic analyses in the GTEx project show sex differences in genetic regulation of gene expression in both reproductive and nonreproductive tissues, providing an important means of evaluating the mechanisms through which sex‐specific genetic loci might act.…”
Section: Sex Differences In Human Genomic Studies Of Addictionmentioning
confidence: 99%
“…We obtained male post-mortem human hippocampal (CA4 to CA1 and 100 dentate gyrus) RNA-sequencing (RNA-seq) data from the Sequence-Read-Archive 101 (accession#: SRA029279). After outlier screening 16 The other half of midbrain samples had no history of drug or cocaine abuse and died 124 from acute causes such as cardiovascular disease or gunshot wounds. Cases and 125 controls were well matched on race and did not differ on RNA integrity (degree of 126 RNA degradation), age and brain pH level, all |t| < 1.04, all p > 0.313.…”
Section: Human Samples 99mentioning
confidence: 99%
“…We utilized data 79 from a recent cocaine use/self-administration study that assessed the 80 transcriptomic alterations in multiple reward circuitry regions in mice 11 . We 81 compared this with two post-mortem studies of individuals diagnosed with CUD 82 versus cocaine-free controls with analogous brain regions -the hippocampus 12 and 83 the midbrain/ventral tegmental area (VTA 13 ) Previous cross-species gene 84 expression studies for substance use have been limited to a single brain region and 85 typically have relied on a limited focus on candidate targets or systems [14][15][16] . Given 86 the etiology of substance use disorders encompasses many neurological substrates 87 and involves a multitude of molecular systems, research is warranted to examine 88 various tissues and assess global convergence across the transcriptome.…”
Section: Introduction 37mentioning
confidence: 99%
“…Interestingly, the TAAR1 gene does not occur in genetic databases referencing addiction or neuropsychiatric disorders associated with dopaminergic pathology. These include databases generated from studies on: 1) subjective responses to amphetamines [49], 2) self-reported alcohol consumption [50], 3) cocaine dependence [51], 4) schizophrenia [17,52], and 5) Parkinson's disease [53]. A recent genome-wide association study (GWAS) that investigated alleles that correlated with shared risk for alcohol (n = 521 participants), heroin (n = 1026 participants), and MA (n = 1749 participants) did not identify TAAR1 [54].…”
Section: Discussionmentioning
confidence: 99%